Valuation of the Coompay: The analysis of the company valuation through computational application. - Liao, Benlung (2007)
Valuation of a company is not an exact science. Price is always the paramount issue as it is the number the seller and buyer are most concern that ultimately determines the final puzzle in completing the transaction that involves the exchange of the ownership between the two parties. This research is to address many problems confronting many investors, especially those with no finance background. The software package is aimed to provide the very first step in approaching the decision making of investment through various model and analysis technique. The main goal of this paper is to build a user-friendly graphical interface for not just the professionals but also the general public. The software package will bring a step closer to the target company from the inside out. This includes the companyÃÆÃÂ¢s net sales to the fair valuation of the share price. The process will layout the forecast of the target company's cash flow and provides analysis to the final valuation within a single graphical interface.